Land-locked: An Examination of Some of the Inefficiencies Affecting Transactions Involving Immovable Property (The Pakistan Development Review, 2006)
In the study of law and economics, the Coase Theorem posits that an efficient allocation of resources will result when transactions costs are zero.1 These “transaction costs” may be viewed as impediments to an efficient allocation of resources and can take many forms. For example, long distances between a prospective vendor and purchaser of property and a lack of communication facilities between them would impede even the best of intentions to enter into a bargain. Similarly, the cost of mobilising labour and materials might impede a property developer from pursuing a tender for civil works. In some cases, a high rate of Stamp Duty on transactions can result in the parties reconsidering their decision to enter into such bargains. To the extent this author can claim knowledge of economics, the Coase Theorem also suggests that transaction costs and inefficiencies hamper the natural flow of bargains, result in inefficient allocation of resources and thus impact the economy. Some transaction costs are small enough to ignore whereas some, imposed, for example, by the law, are unavoidable. In such cases, a mutual understanding between the parties may see the burden of these transaction costs shared or, in others, avoided altogether. For example, the statutory requirements that all leases purporting to grant a term in excess of one year or which reserve an annual rent must be registered and stamped2 often results, in owners of residential property granting indefinitely renewable leases of 11 months and thus avoiding such requirements.